Determinants of establishment size in Irish manufacturing industries - some notes on Irish case 1931-1972 - Farley, Noel J.J. (Economic & Social Studies, 1975)
In recent times economic writing has examined the questions of what determines estabhshment size in manufacturing industries and whether establishment size has increased over time. In 1952 J. Jewkes argued that there was little or no tendency for the size of establishments to increase over time. Using Swedish data, R. G. D. Allen seemed to confirm this finding but P. Sargent Florence laid out the position that there was some tendency for the size of establishments to increase slowly over the decades of the 20th century. Both Jewkes and Florence provided reasons for their findings but the central issue remained unresolved.
Keywords: Manufacturing industry - Size; Manufacturing industry - Growth